Fungsi Pemasaran dan Determinan Utama Kinerja Pemasaran Kakao - Nur Fatinah, Siti; Akbar, Akbar; Sahlan, Sahlan; Jumiati, Jumiati (Jurnal Sosial Ekonomi Pertanian, 2025)
This study aims to analyze the cocoa marketing functions, evaluate the marketing performance, and identify factors influencing cocoa marketing performance in Jauhpandang Village, Pitumpanua Subdistrict, Wajo Regency. The research employs a quantitative and descriptive qualitative approach, utilizing descriptive quantitative data analysis techniques such as marketing margin, farmer,s share, and multiple linear regression analysis. The sampling method used is simple random sampling. Both primary and secondary data are utilized, with data collection carried out through observation, interviews, and documentation. The study involved 32 respondents. The findings indicate that farmers are involved in activities such as sales, transportation, storage, packaging, and accessing market information. Collecting institutions perform functions such as purchasing, selling, storing, transporting, packaging, risk management, and providing market information. Wholesaler institutions carry out purchasing, selling, storing, packaging, and market information activities. The marketing margin is identified as IDR. 9,000/Kg, with cocoa farmers achieving the highest farmer share at 0.98%. Factors influencing cocoa marketing performance in Jauhpandang Village include a positive and significant impact of product innovation and entrepreneurship on marketing performance. However, market orientation was found to have a negative effect on marketing performance